2020
DOI: 10.21037/apm.2020.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Serum iron levels are negatively correlated with serum triglycerides levels in female university students

Abstract: Background: Dyslipidemia is common among the general population, and its prevention is urgently needed particularly for the health of students. The purpose of our study was to explore the relationship between serum iron level and blood lipids.Methods: A sample of 290 university students was collected in this cross-section study. The blood lipids and serum iron levels were determined. Pearson's correlation coefficient was used to determine the correlation between serum iron level and blood lipids.Results: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…1 D). This observation is in agreement with the inferences drawn from a cross-sectional study on 290 individuals wherein He et al 5 found a negative correlation between dyslipidemia (high triglyceride and low high-density lipoprotein cholesterol levels) and serum iron. The absence of excess iron in hypercholesterolemia indicates the prognostic application of excess iron as a marker for the progression of hypercholesterolemia to MetS.…”
Section: Comparison Of Ferroptosis Molecular Mediators In Mets T2d An...supporting
confidence: 91%
“…1 D). This observation is in agreement with the inferences drawn from a cross-sectional study on 290 individuals wherein He et al 5 found a negative correlation between dyslipidemia (high triglyceride and low high-density lipoprotein cholesterol levels) and serum iron. The absence of excess iron in hypercholesterolemia indicates the prognostic application of excess iron as a marker for the progression of hypercholesterolemia to MetS.…”
Section: Comparison Of Ferroptosis Molecular Mediators In Mets T2d An...supporting
confidence: 91%
“…This study also has several limitations: To begin, our study included a smaller sample size. Second, it is reported that serum iron level is negatively correlated with serum triglyceride, 33 and free fatty acids are associated with SLE. 34 Therefore, whether other trace elements are associated with SLE activity and prognosis should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, in a cross-sectional study conducted on 7,540 adults, after adjusting for covariates, the levels of LDL-C were positively related to iron levels [ 64 ]. The results of another cross-sectional study showed that serum iron concentration was positively associated with HDL-C, LDL-C, and TC, but was inversely associated with TG in female students [ 65 ].…”
Section: Discussionmentioning
confidence: 99%